Lugares de memória da educação na cidade de Abaetetuba: a banda marcial da Escola Estadual Pedro Teixeira - OLIVEIRA, João Eduardo Carneiro de (2022)
History as a science contributes not only to the analysis of the past, but also to understanding the present and revolutionizing the future, in this way, we sought to establish the crossings between local history, memory, places of memory and education in the municipality of Abaetetuba. The present research aims to understand how the Banda Marcial da Escola Pedro Teixeira in its historical trajectory can be constituted as a Place of Memory of Education in the municipality of Abaetetuba-PA. Thus, the research has a qualitative approach and presents itself as an educational history, with bibliographic support and the method of oral history. As a theoretical reference we have the contribution of several authors, but I highlight the contribution of Le Goff (1924) and Nora (1984). Therefore, from the theoretical analyses, and from the memories of the former members of the Percussion Band that guide and brighten this research, it is concluded that although the Band is not a crystallized source, it can be considered as a place of memory in education in Abaetetuba.